Inductor shape determination for electromagnetic forming of sheet workpieces - Mikhailov, Valery; Petrenko, Mykyta (Товариство польських інженерів електротехніки та електроніки, 2020)
The method of determining a cross section of an inductor which provides specified distribution of magnetic induction and consequently distribution of deforming forces on a flat sheet workpiece during the electromagnetic forming process is developed. The problem of continuation of a magnetic field from a flat boundary surface of an ideally superconducting half-space with given odd induction distribution is solved. Parameters, which allow us to minimize a difference between given and obtained induction distribution are determined.
Keywords: electromagnetic forming; sheet workpiece; inductor; inductor cross-section